2016
DOI: 10.1039/c6qo00222f
|View full text |Cite
|
Sign up to set email alerts
|

Efficient construction of the A/C/D tricyclic skeleton of palhinine A

Abstract: An efficient approach for the synthesis of the 9/6/6 tricyclic structure ofLycopodiumalkaloid palhinine A has been accomplished. This protocol can undergo ring constriction to rapidly construct the highly strained nine-membered azonane ring of palhinine A.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…This high efficient cascade reaction rapidly resulted in a very similar tetracyclic skeleton of palhinine A 52 in 42% yield. [ 23 ]…”
Section: Total Syntheses Of Lycopodium Alkaloidsmentioning
confidence: 99%
“…This high efficient cascade reaction rapidly resulted in a very similar tetracyclic skeleton of palhinine A 52 in 42% yield. [ 23 ]…”
Section: Total Syntheses Of Lycopodium Alkaloidsmentioning
confidence: 99%
“…Following their successful synthesis in 2012 ( Section 2.1 ), She and coworkers also made many attempts to install the azonane ring on the isotwistane cage, and also encountered great problems. Sandwiching between Fan’s reports in 2016 and 2017, She’s group disclosed their innovative and distinct approach in 2016 [ 19 ]. Different from Fan’s idea, She and coworkers proposed another talent strategy using ring constriction from a large macrocyclic ring system to overcome the inherent strain of the nine-membered medium-sized azonane ring ( Scheme 7 ).…”
Section: Synthetic Efforts Reported During 2016–2020mentioning
confidence: 99%
“…Modifying the functional groups on C3 or C6 did not affect the outcome of the reaction. Previous synthetic studies of the palhinines concluded that the twisted structure of the isotwistane moiety may strain the 9-membered fused ring at its bridgeheads (C4 and C12).…”
mentioning
confidence: 99%